Effects of Packaging with Different Oxygen Resistance Materials on the Quality of Fresh Pork - Xiaoyu CHAI; Dequan ZHANG; Debao WANG; Xin LI; Chengjun MIN; Yuqian XU; Chaoqiao ZHU; Wei YANG; Weili RAO; Chengli HOU (Shipin gongye ke-ji)
To evaluate the effect of different resistance oxygen of packaging materials opposite preservation of fresh meat, pork was packaged with 4 kinds of oxygen resistance grade packaging materials, high (HORP, 1.70 cm3/(m2·24 h·0.1 MPa)), medium (MORP, 23.95 cm3/(m2·24 h·0.1 MPa)), low oxygen resistance (LORP, 1631.44 cm3/(m2·24 h·0.1 MPa)) bags along with oxygen permeable packaging (OPP, 10600.00 cm3/(m2·24 h·0.1 MPa)) in this experiment. Samples were stored at 4 ℃ for 0, 3, 6, 9, 12, and 15 d. The total viable count (TVC), pH, total volatile basic nitrogen (TVB-N) value, water holding capacity, tenderness, protein oxidation and volatile odor of fresh pork during storage were measured and investigated. Results showed that TVC of fresh pork in HORP, MORP, LORP and OPP on 15 d increased to 5.86, 5.72, 6.90 and 7.43 lg CFU/g compared with 0 d (3.82 lg CFU/g) respectively. Compared to OPP group, the increase of TVB-N value and carbonyl group content on 15 d were significantly (P<0.05) inhibited by HORP and MORP group, inhibited protein oxidation of pork during the storage period, the content of total sulfhydryl group in HORP and MORP group was higher than that of OPP group. The microstructure of muscles fibers detected by scanning electron microscope in the HORP and MORP group was observed to have the best structural integrity. The results of electronic nose measurement showed that the response values of fresh pork in all groups to W1W (sensitive to sulfide) and W5S (sensitive to nitrogen oxides) exhibited the greatest differences, and the HORP and MORP group could obviously reduce the production of sulfur and nitrogen oxides in fresh pork during storage. In summary, both HORP and MORP were more suitable for storing fresh pork at 4 ℃. In terms of extending the shelf life, 15 days or more could be expected.